Revision of the alvinocaridid shrimp genus Rimicaris Williams & Rona, 1986 (Decapoda: Caridea) with description of a new species from the Mariana Arc hydrothermal vents - Methou, Pierre; Chen, Chong; Komai, Tomoyuki (Zootaxa, 2024)
A new species of alvinocaridid shrimp is reported, from the Northwest Eifuku hydrothermal vent field at 1619–1667 m depth on the Mariana Arc. A comprehensive phylogenetic reconstruction of Alvinocarididae based on the mitochondrial cytochrome c oxidase subunit I (COI) gene including this new species reveals the paraphyly of the genus Rimicaris Williams & Rona, 1986 with four other genera—Alvinocaridinides, Manuscaris, Opaepele, and Shinkaicaris—nested within it. We re-examine material of these four problematic genera, and synonymise them under Rimicaris whose diagnosis has been amended, in order to maintain a monophyletic Rimicaris. Our new species, Rimicaris cambonae sp. nov. is genetically close to Rimicaris loihi (Williams & Dobbs, 1995) comb. nov. (previously Opaepele loihi) with which it co-occurs, but can be morphologically distinguished by the less elevated dorsal surface of the rostrum, this being devoid of a median carina, a stronger pterygostomial tooth on the carapace, and a blunt rather than acuminate proximolateral process on the antennular stylocerite. Species previously assigned to the above listed, synonymized genera are also discussed, with new material examined for three key species: R. loihi, R. acuminata, and R. leurokolos. Further, Alvinocaridinides formosa Komai & Chan, 2010 and Manuscaris liui Wang & Sha, 2016 are synonymized under Rimicaris leurokolos (Kikuchi & Hashimoto, 2000) comb. nov. and R. acuminata (Komai & Tsuchida, 2015) comb. nov., respectively. Revised diagnoses are presented for R. loihi, R. acuminata, and R. leurokolos. After the present revision revision, Rimicaris now consists of 15 species.